Deposition of tetraferrocenylporphyrins on ITO surfaces for photo-catalytic O2 activation. Issue 37 (27th June 2016) - Sabuzi, F.; Tiravia, M.; Vecchi, A.; Gatto, E.; Venanzi, M.; Floris, B.; Conte, V.; Galloni, P.
Abstract : Tetraferrocenylporphyrins have been successfully deposited on ITO electrodes for O2 photo-catalytic activation. Abstract : Tetraferrocenylporphyrins (TFcPs) are a class of compounds where the porphyrin macrocycle is functionalized with a ferrocenyl group at each of the four meso positions. TFcPs exhibit interesting electrochemical properties, mostly due to electronic communication between the ferrocenyl substituents and the porphyrin core. This leads to their capability to release and accept multiple electrons at distinct potentials through reversible and well distinguished processes. Synthesis of substituted-tetraferrocenylporphyrins containing a carboxylic acid functionality allowed to prepare well packed thin layers of TFcP on ITO electrodes using different deposition techniques. In this context, self-assembled monolayers (SAMs) and Langmuir–Blodgett mono- and multilayers (LBs) of TFcPs have been prepared on ITO surfaces. TFcP-functionalized ITO electrodes showed very high stability, and their application in photocatalytic oxygen activation has been tested.